Engagement in research capability-building: Impact on healthcare workforce attraction and retention in rural and remote Australia – A scoping review protocol - Tsegaye G. Haile; Hilary Wallace; Justin Manuel; Mohamed Estai (PLoS ONE, 2026)
Background Geographic maldistribution of the health workforce remains a major challenge in Australia, with rural and remote communities experiencing persistent shortages that undermine access to and quality of care. Engagement in research is recognised as a potential mechanism for professional growth, continued learning, and improved workplace environments. Providing opportunities for health workers to participate in research or research capability-building (RCB) may therefore support workforce outcomes such as attraction and retention. This scoping review will identify and map existing evidence on the relationship between research engagement and health workforce outcomes in rural and remote Australia, and to summarise the factors that contribute to successful implementation of such initiatives. Methods and analysis We will conduct a scoping review of published and grey literature from Australia (2000 to present). Searches will be undertaken in CINAHL (EBSCO), Embase (Ovid), Global Health (Ovid), MEDLINE (Ovid), and PubMed, following the PRISMA-ScR 2020 guidelines and the Joanna Briggs Institute methodology for scoping reviews. Additional searches will be conducted through Google, Google Scholar, organisational websites, and snowballing of reference lists from included studies. Search terms will address four core concepts: (i) health professionals; (ii) research and RCB; (iii) workforce outcomes; and (iv) rural and remote Australian settings. Both qualitative and quantitative evidence will be included. Data will be synthesised using descriptive and thematic analysis, combining deductive approaches informed by the socioecological model and inductive approaches. Subgroup analyses will be undertaken where appropriate to provide deeper insights into the findings. Ethics and dissemination This scoping review will not involve human participants or primary data collection and does not require ethical approval. The results of this review will be published in a peer-reviewed journal.